Evaluasi Implementasi Perencanaan Pembelajaran PAI Menggunakan Platform Digital: Studi Kasus Madrasah Aliyah - Messidyanto Abdurrohim; Ulil Abshor; Lillatun Ni’mah Salsabila Salsabila; Indah Safira; Sulhatun Naajiyah (Penerbit Minhaj Pustaka, 2026)
The digital era demands changes and adjustments in the implementation of education, including in the planning and implementation of Islamic Religious Education (PAI) learning in Madrasah Aliyah. This article aims to evaluate the implementation of PAI learning planning using digital platforms with a focus on three main aspects, namely: (1) teacher readiness and adaptation in designing digital-based PAI learning planning; (2) utilization of digital platforms in supporting the implementation and evaluation of PAI learning; and (3) various challenges, impacts, and strategic recommendations needed for PAI learning planning to run effectively and sustainably. This research uses a qualitative approach with a case study type through the collection of library data and online qualitative data involving PAI teachers, students, and elements of madrasah management. The results of the study indicate that the implementation of PAI learning planning based on digital platforms has begun and received a relatively positive response from teachers and students, because it is able to increase planning flexibility, the effectiveness of learning implementation, and student involvement in the learning process. However, this implementation still faces various obstacles, such as limited access and technological infrastructure, differences in the digital competency capabilities of teachers and students, technical obstacles in the use of platforms, and less than optimal integration of Islamic values in the planning, implementation, and evaluation of digital-based learning. In conclusion, digitalization of Islamic Religious Education (PAI) lesson planning cannot be interpreted simply as the use of technology, but needs to be directed at strengthening character, spirituality, and the goals of Islamic education. Therefore, it is necessary to improve teachers' digital competencies, align technological infrastructure, develop digital-based PAI content with pedagogical and Islamic values, and plan evaluations that are appropriate to the context of digital learning in Madrasah Aliyah (Islamic Senior High School) environments on an ongoing basis. Abstraksi Era digital menuntut adanya perubahan dan penyesuaian dalam pelaksanaan pendidikan, termasuk dalam perencanaan dan pelaksanaan pembelajaran Pendidikan Agama Islam (PAI) di Madrasah Aliyah. Artikel ini bertujuan untuk mengevaluasi pelaksanaan perencanaan pembelajaran PAI menggunakan platform digital dengan fokus pada tiga aspek utama, yaitu: (1) kesiapan dan adaptasi guru dalam merancang perencanaan pembelajaran PAI berbasis digital; (2) pemanfaatan platform digital dalam mendukung pelaksanaan dan evaluasi pembelajaran PAI; dan (3) berbagai tantangan, dampak, dan rekomendasi strategis yang dibutuhkan agar perencanaan pembelajaran PAI dapat berjalan efektif dan berkelanjutan. Penelitian ini menggunakan pendekatan kualitatif dengan tipe studi kasus melalui pengumpulan data pustaka dan data kualitatif daring yang melibatkan guru PAI, siswa, dan unsur-unsur manajemen madrasah. Hasil penelitian menunjukkan bahwa pelaksanaan perencanaan pembelajaran PAI berbasis platform digital telah mulai dilaksanakan dan mendapat respons yang relatif positif dari guru dan siswa, karena mampu meningkatkan fleksibilitas perencanaan, efektivitas pelaksanaan pembelajaran, dan keterlibatan siswa dalam proses pembelajaran. Namun, implementasi ini masih menghadapi berbagai kendala, seperti keterbatasan akses dan infrastruktur teknologi, perbedaan kemampuan kompetensi digital guru dan siswa, kendala teknis dalam penggunaan platform, dan integrasi nilai-nilai Islam yang kurang optimal dalam perencanaan, implementasi, dan evaluasi pembelajaran berbasis digital. Kesimpulannya, digitalisasi perencanaan pembelajaran Pendidikan Agama Islam (PAI) tidak dapat diartikan hanya sebagai penggunaan teknologi, tetapi perlu diarahkan pada penguatan karakter, spiritualitas, dan tujuan pendidikan Islam. Oleh karena itu, perlu meningkatkan kompetensi digital guru, menyamakan infrastruktur teknologi, mengembangkan konten PAI berbasis digital dengan nilai-nilai pedagogis dan Islam, serta merencanakan evaluasi yang sesuai dengan konteks pembelajaran digital di lingkungan Madrasah Aliyah secara berkelanjutan